Photo Protection of Haematococcus pluvialis Algae by Astaxanthin: Unique Properties of Astaxanthin Deduced by EPR, Optical and Electrochemical Studies - Focsan, A. Ligia (Antioxidants (Basel), 2017)
The antioxidant astaxanthin is known to accumulate in Haematococcus pluvialis algae under unfavorable environmental conditions for normal cell growth. The accumulated astaxanthin functions as a protective agent against oxidative stress damage, and tolerance to excessive reactive oxygen species (ROS) is greater in astaxanthin-rich cells. The detailed mechanisms of protection have remained elusive, however, our Electron Paramagnetic Resonance (EPR), optical and electrochemical studies on carotenoids suggest that astaxanthin’s efficiency as a protective agent could be related to its ability to form chelate complexes with metals and to be esterified, its inability to aggregate in the ester form, its high oxidation potential and the ability to form proton loss neutral radicals under high illumination in the presence of metal ions. The neutral radical species formed by deprotonation of the radical cations can be very effective quenchers of the excited states of chlorophyll under high irradiation.